Kontribusi Dukungan Sosial Teman Sebaya terhadap Motivasi Berprestasi Siswa - Maria Oktasari; Solihatun Solihatun; Monalisa Monalisa (Program Studi Bimbingan dan Konseling FKIP UMSU, 2018)
The research background was the still low level of achievement motivation student. Student perceptions of social support peers is thought to influence the achievement motivation. This research aims to know the perceptions of students on the relationship of social support peers with the achievement motivation. These studies use quantitative methods with regression techniques. The population in this research was sman 1 V Koto Timur Padang Pariaman are numbered 425 people, the sample amounted to 206 people, chosen by Proportional Random Sampling techniques. The instruments used are the Likert scale model. Research findings show that: there was a relationship between of student perception about peers support with achievement motivation.